Physical seed damage, not rodent's saliva, accelerates seed germination of trees in a subtropical forest - Yunlong Zhu; Xifu Yang; Yuwei Teng; Zhenyu Wang; Zhibin Zhang (Ecology and Evolution)
Abstract Many tree species adopt fast seed germination to escape the predation risk by rodents. Physical seed damage and the saliva of rodents on partially consumed seeds may act as cues for seeds to accelerate germination process. However, the impacts of these factors on seed germination rate and speed remain unclear. In this study, we investigated such impacts on the germination rate and speed (reversal of germination time) of four tree species (Quercus variabilis, Q. serrata, Q. acutissima, Q. glauca) after partial consumption by four rodent species (Leopoldamys edwards, Niviventer fulvescens, N. confucianus, Apodemus draco), through a series of experiments. We also examined how seed traits may affect the seed damage degree by rodents by analyzing the relationship between the germination rate and time of rodent‐damaged seed and the traits. We found that, artificially‐ and rodent‐damaged seeds exhibited a significantly higher seed germination rate and speed, compared to intact seeds. Also, the rodent saliva on seeds showed no significant effect on seed germination rate and speed. Furthermore, we observed significant positive correlations between several seed traits (including the seed mass, coat thickness, and protein content) and the seed germination rate and speed. These correlations are likely due to their beneficial traits countering seed damage by rodents. Overall, our results highlight the significant role of physical seed damage by rodents (rather than their saliva) in facilitating seed germination of tree species, and potential mutualism between rodents and trees. Additionally, our results may have some implications in forest restoration, such that intentionally sowing or dispersing slightly damaged seeds by humans or drones may increase the likelihood of successful seed regeneration.